2014
DOI: 10.1186/1465-9921-15-44
|View full text |Cite
|
Sign up to set email alerts
|

The short and long term effects of exercise training in non-cystic fibrosis bronchiectasis – a randomised controlled trial

Abstract: BackgroundExercise training is recommended for non-cystic fibrosis (CF) bronchiectasis, but the long-term effects are unclear. This randomised controlled trial aimed to determine the effects of exercise training and review of airway clearance therapy (ACT) on exercise capacity, health related quality of life (HRQOL) and the incidence of acute exacerbations in people with non-CF bronchiectasis.MethodsParticipants were randomly allocated to 8 weeks of supervised exercise training and review of ACT, or control. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 43 publications
(76 reference statements)
5
136
0
10
Order By: Relevance
“…At the end of treatment, patients in the exercise group had an increase in 62 m in their incremental shuttle walk distance, improved dyspnoea and a reduced time to the next exacerbation and total number of exacerbations over 12 months (median (IQR) 1 (1-3) versus 2 (1-3); p=0.01). This study clearly demonstrates a benefit of exercise to patients with bronchiectasis, but most of the benefits were not sustained to 6 or 12 months suggesting this kind of intervention needs to be continuous to achieve long-term benefits [50].…”
Section: Airway Clearancementioning
confidence: 77%
See 1 more Smart Citation
“…At the end of treatment, patients in the exercise group had an increase in 62 m in their incremental shuttle walk distance, improved dyspnoea and a reduced time to the next exacerbation and total number of exacerbations over 12 months (median (IQR) 1 (1-3) versus 2 (1-3); p=0.01). This study clearly demonstrates a benefit of exercise to patients with bronchiectasis, but most of the benefits were not sustained to 6 or 12 months suggesting this kind of intervention needs to be continuous to achieve long-term benefits [50].…”
Section: Airway Clearancementioning
confidence: 77%
“…A subsequent pilot randomised controlled trial showed improvements in LCQ and SGRQ sustained to 20 weeks after treatment [49]. In a recent randomised controlled trial by LEE et al [50], an 8-week supervised exercise training schedule that include airway-clearance techniques was compared with standard care . 43 patients were randomised to exercise training and 43 to standard care.…”
Section: Airway Clearancementioning
confidence: 99%
“…Although few studies have explored the impact of physiotherapy in bronchiectasis, airway clearance techniques seem to be safe and allow a better sputum expectoration with an increase in patients' quality of life [20]. Evidence on pulmonary rehabilitation is scarce; however, most of the studies demonstrated an increase in patients' performance and quality of life, and an increase of the time to the next exacerbation [21][22][23]. Both physicians and patients agreed that additional controlled trials of these interventions would be beneficial but that the priority may be in identifying methods that are accessible and that encourage adherence.…”
Section: Consensus Statementmentioning
confidence: 99%
“…A dissociation of lung function, dyspnea ratings, and pulmonary extension in bronchiectasis was observed by Martínez-García et al [10] , whereas Lee et al [11] , in an objective assessment of the bronchial tract involved and in a subjective assessment of HRQoL, identified the major determinants of the 6-min walk test (6MWT) in bronchiectasis. These prospective studies on the effect of PR in patients with non-CF bronchiectasis showed short-term improvements in exercise tolerance and HRQoL following a combination of lower limb endurance and strength training (but regardless of inspiratory muscle training) [12] or regular airway clearance therapy [9,13] . Longterm improvements were observed only for the frequency of acute exacerbations and the time to first exacerbation [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for recommending PR to patients with non-CF bronchiectasis relies primarily on physiological reasoning and on the similarities between this disease and COPD [3,5] . Moreover, since the pathophysiology of non-CF bronchiectasis involves more factors than only airflow obstruction, PR might represent a useful tool also for patients without airflow obstruction [9] . A dissociation of lung function, dyspnea ratings, and pulmonary extension in bronchiectasis was observed by Martínez-García et al [10] , whereas Lee et al [11] , in an objective assessment of the bronchial tract involved and in a subjective assessment of HRQoL, identified the major determinants of the 6-min walk test (6MWT) in bronchiectasis.…”
Section: Introductionmentioning
confidence: 99%